Effects of two production systems in the mineral content in the fruit of musa aab simmonds (2011)
Organic and/or ecological production systems aim to ensure the sustainability and renewal of natural base by limiting the use of chemical synthesis products to promote the environment and human health.  Regarding these benefits, we studied the effect of organic and conventional production systems on mineral nutrient contents of the plantain fruit (Musa AAB Simmonds) during the ripening process. Measurements were performed at the University of Córdoba (Montería, Colombia) in order to differentiate the mineral content of fruits between the two systems, and at different stages of maturity. A complete randomized design with 2 x 5 factorial arrangements with five replications was used. The factors were: production system and stage of maturity.  The five levels of the second factor corresponded to the following levels of maturity: dark green (V), light green (VC), yellow-green (AV), yellow (A) and very yellow (MA). The results showed that the two production systems and the different degrees of maturity had significant differences (P and lt; 0.05) in Calcium, Magnesium, Potassium, Sodium, Iron and Zinc contents.